The Russian-Ukrainian war of 2014-2022: Monitoring of state-confessional relations in Ukraine - Анатолій Колодний; Людмила Филипович (Cхід, 2022)
The article examines the changes that have taken place in religious life in Ukraine since the beginning of the Russian-Ukrainian war. In particular, it describes how the unlawful forceful occupation of the territory of a sovereign state has led to the restructuring of the Ukrainian confessional landscape and mass migration of Ukrainian confessionals of different faiths. Based on data from open sources, the authors present the position of the most influential confessions in Ukraine and their leaders on the Russian-Ukrainian war. The authors prove that the war-affected intensification of the identification processes in the religious segment of Ukrainian society has affected state-confessional relations in the country, and now society needs clear, consolidating messages from the state more than ever. The recommendations provided by the authors determine that the state and religious organisations ought to dynamically strengthen their partnership, develop new forms of relations, and jointly preserve religious pluralism and freedom of religion. The issues of state re-registration of all religious structures of Ukraine, including their social characteristics and the nature of relations with foreign religious centres, and creating a public Scientific Expert Council on security in the humanitarian sphere are also being considered. In order to protect the national information and spiritual environment, the state initiated the study of confessional periodicals of Ukraine and printed materials imported from abroad for distribution among Ukrainian religious believers. The state, according to the authors of the article, has to initiate amendments to the current Law on Freedom of Conscience and Religious Organisations that exercises the principle of religious separation of the church from the state and school, as well as the establishment of penalties for religious activities that harm the national and state security of the Ukrainian people.